History of the "Green City" in Russia - Yanitsky, Oleg; Usacheva, Olga (Journal of History Culture and Art Research, 2017)
This paper deals with the stages of the development of the green city concept by Russian authors for 100 years. It is noted that these concepts have always been associated with the dominant ideology and socio-economic processes. Due to fundamental changes in the social structure of Russia and a number of critical states (wars, changing types of social production), the linear trajectory of the development of the concept of a "green city" in Russian science and practice could not have developed. Throughout the years there has been a struggle between two social and town-planning concepts: urbanization and de-urbanization, the desire for socialization of everyday life and its individualization. The development of the concept and programs of "greening" of Russian cities continues today, taking into account modern realities.